Real-time monitoring of electrochemical controlled protein adsorption by a plasmonic nanowire based sensor - Pallarola, Diego; Schneckenburger, Manuel; Spatz, Joachim P.; Pacholski, Claudia (Chemical communications, 2013)
A plasmonic sensor composed of a vertically aligned gold nanowire array was fabricated and employed for the optical detection of protein adsorption induced by an electric field.
Gesehen am 16.12.2013